Genome-wide characterization of Mariner-like transposons and their derived MITEs in the Whitefly Bemisia tabaci (Hemiptera: Aleyrodidae). Issue 12 (2nd September 2021) - Zidi, Marwa; Denis, Françoise; Klai, Khouloud; Chénais, Benoît; Caruso, Aurore; Djebbi, Salma; Mezghani, Maha; Casse, Nathalie
Abstract: The whitefly, Bemisia tabaci is a hemipteran pest of vegetable crops vectoring a broad category of viruses. Currently, this insect pest showed a high adaptability and resistance to almost all the chemical compounds commonly used for its control. In many cases, transposable elements (TEs) contributed to the evolution of host genomic plasticity. This study focuses on the annotation of Mariner- like elements (MLEs) and their derived Miniature Inverted repeat Transposable Elements (MITEs) in the genome of B. tabaci . Two full-length MLEs belonging to mauritiana and irritans subfamilies were detected and named Btmar1.1 and Btmar2.1, respectively. Additionally, 548 defective MLE sequences clustering mainly into 19 different Mariner lineages of mauritiana and irritans subfamilies were identified. Each subfamily showed a significant variation in MLE copy number and size. Furthermore, 71 MITEs were identified as MLEs derivatives that could be mobilized via the potentially active transposases encoded by Btmar 1.1 and Btmar2.1 . The vast majority of sequences detected in the whitefly genome present unusual terminal inverted repeats (TIRs) of up to 400 bp in length. However, some exceptions are sequences without TIRs. This feature of the MLEs and their derived MITEs in B. tabaci genome that distinguishes them from all the other MLEs so far described in insects, which have TIRs size ranging from 20 to 40 bp. Overall, our study provides an overview of MLEs, especially those with large TIRs, and their related MITEs, as well as diversity of their families, which will provide a better understanding of the evolution and adaptation of the whitefly genome.